1996
DOI: 10.1074/jbc.271.5.2491
|View full text |Cite
|
Sign up to set email alerts
|

β*, a UV-inducible Shorter Form of the β Subunit of DNA Polymerase III of Escherichia coli

Abstract: Control elements located inside the coding sequence of dnaN, the gene encoding the ␤ subunit of DNA polymerase III holoenzyme, direct the synthesis of a shorter and UV-inducible form of the ␤ subunit (Skaliter, R., Paz-Elizur, T., and Livneh, Z. (1996) J. Biol. Chem. 271, 2278 -2281, and Paz-Elizur, T., Skaliter, R., Blumenstein, S., and Livneh, Z. (1996) J. Biol. Chem. 271, 2282-2290). The protein, termed ␤*, was overproduced using the phage T7 expression system, leading to its accumulation as inclusion bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This involvement of the ␤ subunit in UV irradiation effects prompted us to examine whether it may be present in a different form in UV-irradiated cells. Here and in two companion studies (27,28), we report that UV irradiation induces a shorter form of the ␤ subunit that functions in vitro as an alternative DNA polymerase clamp. We suggest that this protein functions in DNA synthesis associated with post-UV recovery in E. coli.…”
mentioning
confidence: 82%
“…This involvement of the ␤ subunit in UV irradiation effects prompted us to examine whether it may be present in a different form in UV-irradiated cells. Here and in two companion studies (27,28), we report that UV irradiation induces a shorter form of the ␤ subunit that functions in vitro as an alternative DNA polymerase clamp. We suggest that this protein functions in DNA synthesis associated with post-UV recovery in E. coli.…”
mentioning
confidence: 82%
“…␤* was purified from an overproducer strain that was constructed in our laboratory (49). Anti-␤ antibodies were affinitypurified on ␤* immobilized on nitrocellulose as previously described (48).…”
Section: Methodsmentioning
confidence: 99%
“…The intact ␤ subunit forms a ␤ 2 ring-shaped sliding DNA clamp, that confers high processivity on DNA polymerase III holoenzyme by tethering it to the DNA (41,42). As shown in a companion study (49), ␤* forms an alternative DNA clamp for DNA polymerase III that may have a specialized function connected to DNA synthesis in the UVirradiated cell. The increase in UV resistance caused by overproducing ␤* is consistent with such a model (48).…”
Section: Dnan* Gene Expression and Regulationmentioning
confidence: 99%
“…The gene for ␤*, which is contained entirely within the dnaN ϩ gene, has been termed dnaN* (39,50). Biochemical characterization of ␤* indicates that it can form a trimer in solution (49). Furthermore, in vitro studies have demonstrated that ␤* can modestly enhance the processivity of Pol III*, a form of Pol III containing all subunits except the ␤ clamp (49).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical characterization of ␤* indicates that it can form a trimer in solution (49). Furthermore, in vitro studies have demonstrated that ␤* can modestly enhance the processivity of Pol III*, a form of Pol III containing all subunits except the ␤ clamp (49). However, despite these detailed genetic and biochemical analyses, the physiological role of ␤* is presently unknown.…”
Section: Discussionmentioning
confidence: 99%